2016
DOI: 10.1002/slct.201600298
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Cd1-xZnxS (x=0-1) Nanoparticles by Thermal Decomposition of Bis(thiourea)cadmium-zinc acetate Complexes

Abstract: The present study reports synthesis of a complete series of Cd1‐xZnxS solid solution nanoparticles (x=0‐1) via thermal decomposition of bis(thiourea)cadmium‐zinc acetate complexes. First, bis(thiourea)cadmium‐zinc acetate complexes were synthesized which were then decomposed at 200 °C for 1 h in diphenyl ether. The bis(thiourea)cadmium‐zinc acetate complexes and Cd1‐xZnxS nanoparticles were characterized using different analytical techniques. The crystallite size of Cd1‐xZnxS nanoparticles varies from 2.1 nm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The IR spectra of pure SnS 2 and the doped samples show bands at about 3350, 3147 and 1617 cm −1 , attributed to asymmetric and symmetric hydroxyl stretching and bending vibration, respectively which indicate that physisorbed water molecules are present in iron doped SnS 2 nanoparticles [34,46] . The IR band observed at about 1516 cm −1 is due to asymmetric stretching of C−N (ν C‐N ) and the bands at about 1268 and 790 cm −1 are ascribed to asymmetric stretching (ν C‐S ) and bending vibration (δ C‐S ) of C−S, respectively [34,47] . The IR band attributed to bending vibration of C−H group (δ C‐H ) is observed at about 1392 cm −1 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The IR spectra of pure SnS 2 and the doped samples show bands at about 3350, 3147 and 1617 cm −1 , attributed to asymmetric and symmetric hydroxyl stretching and bending vibration, respectively which indicate that physisorbed water molecules are present in iron doped SnS 2 nanoparticles [34,46] . The IR band observed at about 1516 cm −1 is due to asymmetric stretching of C−N (ν C‐N ) and the bands at about 1268 and 790 cm −1 are ascribed to asymmetric stretching (ν C‐S ) and bending vibration (δ C‐S ) of C−S, respectively [34,47] . The IR band attributed to bending vibration of C−H group (δ C‐H ) is observed at about 1392 cm −1 .…”
Section: Resultsmentioning
confidence: 97%
“…[34,46] The IR band observed at about 1516 cm À 1 is due to asymmetric stretching of CÀ N (ν C-N ) and the bands at about 1268 and 790 cm À 1 are ascribed to asymmetric stretching (ν C-S ) and bending vibration (δ C-S ) of CÀ S, respectively. [34,47] The IR band attributed to bending vibration of CÀ H group (δ C-H ) is observed at about 1392 cm À 1 . These IR bands are attributed to thiocyanates and HCNS which are present on the surface of Sn 1-x Fe x S 2 nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…CHNS analysis of the cadmium complex yields 14.8% N, 18.6% C, 3.1% H and 16.5% S, which is in good agreement with the expected values (14.6% N, 18.8% C, 2.6% H and 16.7% S). TGA pattern of the cadmium complex (Figure S2) shows a first weight loss of ∼53% due to decomposition of the complex in the temperature range of 140–250 °C . The second weight loss (∼ 13%) observed in the range of 250–560 °C is attributed to partial oxidation of CdS to CdS.CdO.…”
Section: Resultsmentioning
confidence: 99%
“…TGA pattern of the cadmium complex ( Figure S2) shows a first weight loss of ∼ 53% due to decomposition of the complex in the temperature range of 140-250°C. [36] The second weight loss (∼ 13%) observed in the range of 250-560°C is attributed to partial oxidation of CdS to CdS.CdO. The third step with weight gain (∼ 1.7%) from 580 to 620°C is attributed to partial oxidation of CdS to CdS.CdSO 4 .…”
Section: Bis(thiourea)cadmium Acetate Complexmentioning
confidence: 92%
“…Morphology-dependent studies on nanomaterials have revealed that the same material with different morphologies exhibits significantly different properties [12,13]. Research is being conducted in this direction to tune the morphology and surface characteristics by chemical methods.…”
Section: Introductionmentioning
confidence: 99%